THE PROSPECTS OF ASEAN ECONOMIC COMMUNITY - Wahyudi Wibowo (Journal of Economics, Business, and Accountancy Ventura, 2013)
The world trading environment has changed during the last three decades, especially on the increasingtendency of regionalization. While ubiquitous regionalization is regarded as the newnecessity, recent studies provide mixed views on the effectiveness of the current development ofeconomic integration among the member countries of Association of Southeast Asian Nations(ASEAN). ASEAN regionalization has been commenced through AFTA in 1992 and recentlyASEAN is moving toward further economic integration under the ASEAN Economic Community(AEC), which is planned to be implemented by 2015. Based on the characteristics of the ASEANtrade and investments, this research provides an outlook on the prospect of AEC. First, it providespicture related to the tendency of each of the ASEAN members in regard to their tradingpatterns. Second, it provides the outlook concerning the current structure and developmentalphases of the ASEAN economies. Finally, it provides information about the gaps of developmentamong the ASEAN economies, particularly between the ASEAN-6 and the ASEAN-CLMV.